Formação-Ação: um estudo do desenvolvimento do protagonismo juvenil no projeto missão jovem - Zanella, Renata (2009)
This work presents the contributions of Projeto Missão Jovem (MJ) in the formation of adolescents from Pastoral da Juventude. It proposes the discussion of how the juvenile leadership is stimulated during the course Escola da Juventude in order to motivate them to complete the missionary action. The research was developed in a qualitative way, using as method the case study of the project of the Vicariate of Gravataí in 2008. A camp diary was produced after the conclusion of each stage of the project. Taking into consideration the data, it has been elaborated an analysis that established the following categories: youth, juvenile leadership, formation, transforming mission. Theology and Pedagogy have contributed to the theoretical support of this study. The reflection points to three important stages of MJ. The first is the moment of formation. The course that is organized by young people aims to work the distinct dimensions of them in order to promote an integral formation, using The Book of Christ as the theological basis. The second stage is the moment of action. This stage is characterized by the juvenile leadership. Students challenge themselves to put into practice their projects, assuming a new concept of transforming mission. The intervention in the social context occurs in the collective action. The missionary action is a moment of formation and transformation. The last stage is the moment of transformation in which they establish new paradigms in their life projects that are based on solidarity, collective work, and in the belief that they can make a difference in society as Christian juveniles and participative citizens.